Kompetensi Tutor Dalam Meningkatkan Motivasi Warga Belajar Pada Pusat Kegiatan Belajar Masyarakat Aksara Pangkalpinang - Heriyadi, Heriyadi (Sekolah Tinggi Agama Islam Babussalam Sula, 2022)
This study departs from the problem of the lack of competence of tutors at PKBM AKSARA Pangkalpinang in increasing the learning motivation of learning citizens. This research was conducted to determine the competence of tutors at PKBM AKSARA Pangkalpinang in increasing the learning motivation of learning citizens. This research method uses a qualitative approach. The Instruments are interview and observation. Data were analyzed through data reduction, data presentation and data verification and drawing conclusions. The results showed that the motivation of citizens to learn at PKBM AKSARA Pangkalpinang was good because it was influenced by a good environment. The results showed that the competence of the tutor was very good. Tutors are very helpful in learning, learning citizens can meet all their needs in the teaching process. With a good learning process, the learning motivation obtained by citizens is very good. The conclusion of this study is tutors competence is very necessary to increase the learning motivation of learning citizens in order to achieve learning objectives. Motivating learning residents to always study hard by earnestly gaining knowledge. Motivation is also done by giving rewards to the students who always study hard.